Intercellular communication network of CellChat uncovers mechanisms of kidney fibrosis based on single-cell RNA sequencing - Lei, Lei; Xiang, Yun-Xiu; Luo, Mao-Lin; Zhang, Ze-Yu; Wu, Hong-Wei; Tang, Chun; Cui, Tian-Jiao; Zhang, Xue-Mei; Wang, Xiao-Hua; Delic, Denis; Klein, Thomas; Liu, Yvonne; et al. (Kidney & blood pressure research, 2025)
Background: Chronic kidney disease (CKD) is a global health concern, with renal fibrosis being a major pathological feature. Empagliflozin (Empa), a sodium-glucose co-transporter-2 inhibitor, has shown promise in protecting the kidney. This study aimed to investigate the effects of Empa on renal fibrosis in a nondiabetic CKD model and to elucidate the underlying mechanisms. Methods: We established a CKD model using 5/6 nephrectomy (5/6 Nx) rats and divided them into three groups: placebo-treated sham surgery rats, placebo-treated 5/6 Nx rats, and Empa-treated 5/6 Nx rats. Kidney function was assessed by measuring blood urea nitrogen, serum creatinine, and urinary albumin-to-creatinine ratio. Renal fibrosis was evaluated histologically. Single-cell RNA sequencing (scRNA-seq) was performed to analyze intercellular communication networks and identify alterations in ligand-receptor pairs and signaling pathways involved in fibrosis. Results: Empa treatment significantly improved kidney function and reduced renal interstitial fibrosis in 5/6 Nx rats. scRNA-seq revealed that Empa modulated the TGF-β signaling pathway, inhibited intercellular communication, and reduced the expression of fibrotic genes such as COLLAGEN, FN1, THBS, and LAMININ. Furthermore, Empa downregulated GRN gene expression, weakened signal transmission in the MIF pathway, consequently reduced the interaction between M2 macrophages and other cell types, such as endothelial cells, fibroblasts, and mesangial cells. Conclusion: This study elucidates the potential mechanisms by which Empa slows the progression of renal fibrosis in nondiabetic CKD. By reducing the number of M2 macrophages and inhibiting signal transduction in both pro-inflammatory and fibrotic pathways, Empa modulates the intercellular communication network in renal cells, offering a promising therapeutic strategy for CKD management.